KEBIJAKAN REDAKSIONAL HARIAN UJUNG PANDANG EKSPRES (UPEKS) DALAM MENENTUKAN BERITA HEADLINE DI ERA DIGITAL - Amaliyah Asitomo , Ridha; Majid, Abd; Idris, Muhammad (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to find out how the working mechanism of the Ujung Pandang Express Daily (Upeks) in determining the coverage issues that will be raised as Headline news and what are the factors that influence the determination of Headline news. The type of research used is qualitative research. This study uses two types of theories, namely the Agenda Setting Theory and the Hierarchy of Influence Theory. The results of this study concluded that the determination of Headline news before it was determined had to go through a working mechanism, namely 1). Editorial meeting, 2). Coverage, 3). Editing, 4) determination of news headlines. In addition, there are factors that influence the determination of headline news, namely internal factors and external factors. 1). Internal factors in the media relate to the interests of media owners, individual journalists as news seekers, media organization routines, 2). External factors that influence media content relate to advertiser companies, and technology